Behavior of Reinforced Composite Foamed-Normal Concrete Beams - Angham Nassar Jaffal; Ameer A. Hilal; Akram S. Mahmoud (Journal of Engineering)
A study has been undertaken to investigate the production and behavior of beams made with foamed, normal, and composite concrete and reinforced with different steel percentages (under, balanced, and over). Nine reinforcement beams, including three normal-weight concrete, three lightweight foamed concrete, and three composite concrete, were made with similar rectangular cross sections of dimensions (150 × 250 mm) and length of 1500 mm. A 28-day compressive strength of 29 MPa (suitable for structural purposes) was achieved for all investigated concrete mixes. Ultimate load, crack mode, ductility, deflection, and stiffness as flexural parameters were investigated. The results showed that in terms of loading, the load of composite concrete beams was equal to that of normal concrete beams, and a slight increase in the lightweight foamed concrete beams was noticed. The ductility of foamed concrete beams with balanced reinforcement and under reinforcing was lower than that of normal concrete. In the case of the over-reinforcement beams, the ductility of foamed concrete beam increased by about 19.5% compared to that of normal reinforced concrete. In addition, the ductility and stiffness of composite concrete beams increased by about 91.7% and 5.6% compared to normal beams and 61% and 15.1% compared to foamed concrete beams, respectively.